Isolation of Salmonella enterica Serovar Enteritidis in Blue-Fronted Amazon Parrot (Amazona aestiva) - Marietto-Goncalves, Guilherme Augusto [UNESP]; de Almeida, Silvia Maria [UNESP]; de Lima, Edna Tereza [UNESP]; Okamoto, Adriano Sakai [UNESP]; Pinczowski, Pedro [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Amer Assoc Avian Pathologists, 2010)
Avian salmonellosis is a disease caused by bacteria of the genus Salmonella that can cause three distinct diseases in birds: pullorum diseases, fowl typhoid, and paratyphoid infection. Various wildlife species are susceptible to infections by Salmonella, regardless of whether they live in captivity or freely in the wild. The present study verified the presence of Salmonella enterica serovar Enteritidis in three captive specimens of Amazona aestiva. The study involved a total of 103 birds undergoing rehabilitation to prepare for living in the wild, after having been captured from animal traffickers and delivered to the Centrofauna Project of the Floravida Institute in São Paulo, Brazil. This is the first report of Salmonella Enteritidis isolation in A. aestiva that originated from capture associated with animal trafficking; Salmonella was detected during the study by the serologic method of rapid serum agglutination on a plate with bacterial isolate. The antimicrobial profile exam of the isolated samples demonstrated sensitivity to ampicillin, cefaclor, ciprofloxacin, and cloranfenicol. The three samples also presented resistance to more than four antibiotics. The presence of the genes invA and spvC was verified by PCR technique and was associated with virulence and absence of class 1 integron, a gene related to antimicrobial resistance. The commercial antigen for pullorum disease was shown to be a useful tool for rapid detection in the screening of Salmonella of serogroup D(1) in Psittaciformes. New studies on Salmonella carriage in birds involved in trafficking must be performed to better understand their participation in the epidemiologic cycle of salmonellosis in humans and other animals.
Keywords: salmonellosis; birds; psittacines; avian pathology